(untitled) (Research, Society and Development, 2022)
Objectives: evaluate the effective doses and organ doses from exposure of pediatric patients undergoing CT scans using the Virtual Dose® software. Methods: quantitative, retrospective study, consisting of a random sample of CT scans performed in pediatric patients of both genders, aged 0 to 18 years, from September to December 2020, obtained through the Santa Catarina Telemedicine and Telehealth System (STT). The following secondary data were collected through the DICOM header: kVp, mAs, pitch, slice thickness, scan length, gender, and age group. After collected the data were entered into the Virtual Dose® version 1.0 software for calculation of absorbed dose and effective dose. Results: Of the 100 exam samples collected, 35 exams met the inclusion criteria. The most frequently performed protocols in the period in question were total abdomen/abdomen and pelvis 88.6%, and upper abdomen 8.6%. The mean value of effective doses for abdominal CT scans was 4.35mSv. The age group between 7-10 years received the highest effective dose, 5.09 mSv on average, followed by the 11-14 years group with 4.58 mSv on average. The age group between 0-6 years corresponded to the exams with the lowest effective dose 3.14 (± 0.7) mSv on average. Conclusions: It was observed that the radiation dose received by patients in abdominal CT scans are within the values reported in the literature, but that further studies need to be done to establish the culture of registration and optimization of doses of exposed patients.